The Comparison Of Outcome In Engaged Versus Unengaged Fetal Heads In Primigravida - Sadaf Asma; Sidra Tul Muntaha; Faiza Haq; Sara Hayat; Mona Kanwal (Journal of Rawalpindi Medical College, 2023)
Objective: Our study aimed to compare the outcome of engaged versus unengaged fetal head in primigravida at term. Methods: The study was conducted at the obstetrics & gynaecology unit, FGPC Hospital, Islamabad. The duration of the study was 6 months with a total of 130 women included & divided into two groups. Females were followed till the delivery of the fetus.